Accuracy comparison of post-processed PPP and real-time absolute positioning techniques. Issue 1 (1st January 2020) - Alkan, Reha Metin; Erol, Serdar; Ozulu, I. Murat; Ilci, Veli
Abstract: The main motivation of this study is to assess the accuracy performance of the real-time global GNSS PPP positioning service, i.e. Trimble CenterPoint RTX, and online PPP post-processing service, i.e. CSRS-PPP, in Çorum Province of Turkey. Within this scope, a geodetic point was established and GNSS data were logged in static mode at a measurement interval of 1 Hz. At the same time, the real-time coordinates of each measurement epoch were determined with the Trimble CenterPoint RTX positioning service using L-band geostationary satellite delivery. The collected GNSS data were also sent to the CSRS-PPP service and the coordinates of each measurement epoch were calculated. According to comparison of the coordinates obtained from CenterPoint RTX to the known coordinates, it was concluded that the 3D real-time positioning achieved at centimeter-level of accuracy within convergence time of a few minutes. On the other hand, CSRS-PPP also provided centimeter-level accurate positioning with post-processing mode. The overall results show that, the attainable accuracy with both approaches provided the requirements of the many scientific and practical surveying applications.